OC-014 FAVOURABLE OUTCOMES AFTER RETRO-RECTUS (RIVES-STOPPA) MESH REPAIR AS TREATMENT FOR NON-COMPLEX VENTRAL ABDOMINAL WALL HERNIA, A SYSTEMATIC REVIEW AND META-ANALYSIS. (13th October 2022) - Den Hartog, F; Sneiders, D; Darwish, E; Yurtkap, Y; Menon, A; Muysoms, F; Kleinrensink, G J; Bouvy, N; Jeekel, J; Lange, J
Abstract: Aim: Ventral abdominal wall hernia is a common problem, tied to increasing frailty and obesity of patients undergoing surgery. For noncomplex ventral hernia, retro-rectus (Rives-Stoppa) repair is considered the gold standard. Level-1 evidence confirming this presumed superiority is lacking. The aim of this study was to assess prevalence of hernia recurrence, surgical site infection (SSI), seroma, serious complications, and mortality. Material & Methods: Five databases were searched for studies reporting retro-rectus repair. Randomized and non-randomized studies were included. Outcomes were pooled with random-effects models. Results: Ninety-three studies representing 12, 440 patients undergoing retro-rectus repair were included. Pooled hernia recurrence was estimated at 3.2% [95% confidence interval (CI): 2.2%–4.2%, n = 11, 049] after minimally 12 months and 4.1%, (95%CI: 2.9%–5.5%, n = 3830) after minimally 24 months. Incidences of SSI and seroma were estimated at respectively 5.2% (95%CI: 4.2%–6.4%, n = 4891) and 5.5% (95%CI: 4.4%–6.8%, n = 3650). Retro-rectus repair was associated with lower recurrence rates compared to onlay repair (odds ratios (OR): 0.27, 95%CI: 0.15–0.51, P < 0.001) and equal recurrence rates compared to intraperitoneal onlay mesh (IPOM) repair (OR: 0.92, 95%CI: 0.75–1.12, p = 0.400). Retro-rectus repair was associated with more SSI than IPOM repair (OR: 1.8, 95%CI: 1.03–3.14, p = 0.038). Minimally invasive retro-rectus repair displayed low rates of recurrence (1.3%) and SSI (1.5%), albeit based on non-randomized studies. Conclusions: Retro-rectus repair results in excellent outcomes, superior or similar to other techniques for all outcomes except SSI. The latter occurred less after IPOM repair, which is usually laparoscopic.